2012
DOI: 10.1177/1071181312561149
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Texting and Driving on Hazard Perception

Abstract: Hazard perception has received little attention compared to measures of vehicle control in studies exploring the effects of texting on driving performance, despite being a more direct measure of crash risk. Furthermore, the driver strategies attempting to moderate such distraction are not well understood. The current study attempts to address these two facets of texting while driving. Participants (10 male; 10 female) drove a low fidelity simulator that measures situational awareness, while text messaging in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 17 publications
(25 reference statements)
0
8
0
Order By: Relevance
“…In the context of driving, being more liberal could be beneficial as the consequence of missing a target (e.g., missing a stop sign or a pedestrian could lead to serious crashes) is much worse than making a false alarm (e.g., a driver thought there was a target and slowed down or stopped, which may reduce travel efficiency). Previous research has found that when drivers engaged in a phone conversation, they showed an increased number of false alarms in a hazard perception task, which helped them in missing fewer hazards (Burge & Chaparro, 2012; Savage, Potter, & Tatler, 2013). Similarly, older participants in our study were likely compensating their reduced sensitivity to the task at the higher traffic load condition with a more liberal response criterion.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of driving, being more liberal could be beneficial as the consequence of missing a target (e.g., missing a stop sign or a pedestrian could lead to serious crashes) is much worse than making a false alarm (e.g., a driver thought there was a target and slowed down or stopped, which may reduce travel efficiency). Previous research has found that when drivers engaged in a phone conversation, they showed an increased number of false alarms in a hazard perception task, which helped them in missing fewer hazards (Burge & Chaparro, 2012; Savage, Potter, & Tatler, 2013). Similarly, older participants in our study were likely compensating their reduced sensitivity to the task at the higher traffic load condition with a more liberal response criterion.…”
Section: Discussionmentioning
confidence: 99%
“…Driving performance was measured by commonly used dependent variables (see a review by Caird et al, 2014), including the standard deviation of lane position (SDLP, He et al, 2014a,b;Hosking et al, 2009), the number of lane excursions (Alosco et al, 2012;Crandall and Chaparro, 2012;Hosking et al, 2009), steering behavior (Dingus, 1995;McLaughlin et al, 2009), speed (Strayer and Drew, 2004), headway distance (Drews et al, 2009;Hosking et al, 2009;He et al, 2014a,b), and braking response (Burge and Chaparro, 2012;Drews et al, 2009). A large SDLP and a high number of lane excursions indicate poor lane-keeping performance.…”
Section: Dependent Variablesmentioning
confidence: 99%
“…For example, texting while driving increases hazard response time (Burge & Chaparro, 2012;Drews et al, 2009;He et al, 2014;Leung, Croft, Jackson, Howard, & Mckenzie, 2012), increases lane deviations (the difference between the center of the vehicle and the center of the appropriate lane) and lane excursions (leaving the lane unintentionally) (Alosco et al, 2012;Crandall & Chaparro, 2012;Hosking et al, 2009;McKeever, Schultheis, Padmanaban, & Blasco, 2013;Rudin-Brown, Young, Patten, Lenné, & Ceci, 2013), increases mental demand (mental demands are psychological and mental stress experienced by an individual while completing one or more tasks) (Owens et al, 2011;Rudin-Brown et al, 2013), increases gaze-off-road durations (Hosking et al, 2009;Libby, Chaparro, & He, 2013;Owens et al, 2011), causes more collisions (Alosco et al, 2012;Drews et al, 2009), and raises the risks of traffic accident as many as 8-23 times (Olson, Hanowski, Hickman, & Bocanegra, 2009).…”
Section: Introductionmentioning
confidence: 99%